Pengaruh Pendidikan Kesehatan Tentang Teknik Menyusui Terhadap Pengetahuan Pada Ibu Hamil Trimester III Di Wilayah Kerja Puskesmas Baki Sukoharjo - Lidiyana, Ika Arif; , Dr. Faizah Betty Rahayuningsih A., S.Kep, M.Kes (2017)
Introduction The ignorance of mother about breast-feeding techniques will have an impact on breast-feeding. The causes improper feeding technques so the main cause of failure to breastfeed. The effort to increase knowledge of mother with the provision of health education about breastfeeding is one of the strategic measures to improve the quality of breast-feeding so the baby's growth can be maximized. This study aimed to determine the effect of health education on knowledge about breastfeeding techniques in pregnant women in the third trimester in the public health work Baki, Sukoharjo. This research method is a pre-experimental, with one group pre and post test design. The study samples was 48 third trimester pregnant women obtained by purposive sampling techniques. Data collecting using questionnaires and analyzed using the Wilcoxon Signed Rank Test. The results showed an average knowledge of pregnant women before being given health education on breast-feeding techniques amounted to 59,50 and the average knowledge of pregnant women after healt education given at 77,17 with significant value of 0,000 or p<0,05. The limitiation in this study is less conducive environment and crowded. Place of delivery of health education at the village hall pavilion near the highway so that the concentration of respondents pregnant women receiving less than the maximum. The conclusions shows the influence of health education breastfeeding techniques to pregnant women in the third trimester in the public health service work Baki, Sukoharjo. Suggestions to health centers is improving of research, programs, and the use of media in the provisions of training to improve coverage of exclusive breastfeeding. Education institutions provide an opportunity to improve their skills in providing health education to the community. Researchers can the continue researc samples and expand the area of research, adding other factors associated with maternal knowledge about breastfeeding techniques.